EZH2, HIF-1, and Their Inhibitors: An Overview on Pediatric Cancers - Papale, Marco; Ferretti, Elisabetta; Battaglia, Giuseppe; Bellavia, Diana; Mai, Antonello; Tafani, Marco (Frontiers in Pediatrics, 2018)
During the past decades several discoveries have established the role of epigenetic modifications and cellular microenvironment in tumor growth and progression. One of the main representative concerning epigenetic modification is the Polycomb group (PcG). It is composed by different highly conserved epigenetic effectors proteins preserving through several post-translational modifications of histones, the silenced state of genes implicated in a wide number of central biological processes including cellular development, stem cell plasticity and tumor progression. PcG proteins can be divided in two multimeric protein complexes called Polycomb Repressive Complexes: PRC1 and PRC2. In particular, Enhancer of zeste homolog 2 (EZH2), the catalytic core subunit of PRC2, acts as epigenetic silencer of several tumor suppressor genes by catalyzing the trimethylation of lysine 27 on histone H3, an essential binding site for DNA methyl transferases and histone deacetylases. A growing number of data suggests that over-expression of EZH2 could be deeply associated with cancer progression and poor outcome in a large number of cases. The other master regulator in cancer progression is the Hypoxia Inducible Factor (HIF) that plays a crucial role in modulating cellular response to microenvironment by promoting and regulating tumor development such as angiogenesis, inflammation, metabolic reprogramming, invasion and metastatic fate. HIF complex is represented by different subunits (α and β) acting together and promoting the expression of specific genes such as Vascular Endothelial Grow Factor (VEGF), Hexokinase II (HKII), Receptor for Advanced Glycation End products (RAGE), Carbonic Anhydrase (CA), etc., after the binding to their HRE binding site on the DNA. In this review we will try to connect these two players by detailing: i) the activity and the influence of these two important regulators of cancer progression in particular for what concerns pediatric tumors, ii) the possible correlation between them and, iii) the feasibility and efficiency to contrast them using several inhibitors.